Evaluation of Meshing Quality of Antenna Base Gear Tooth Surfaces Based on the Linear Weighted Gray-scale - Zhang Liu; Qiu Bao'an; Sun Pan; Li Lin; Wang Liming; Shao Yimin (Jixie chuandong)
In order to evaluate the meshing quality of antenna base gears, a method based on the image linear weighted gray-scale was proposed. In this method, the original image of the contact marks in the gear meshing area was collected by CCD cameras. Then, a set of real-time image processing system was built. Aiming at the edge blur problem of traditional adaptive weights graying in different lighting environments, a linear weighted gray-scale image preprocessing method was proposed to enhance target color component. Through the steps of image segmentation and mathematical morphology feature extraction, the relevant parameters reflecting the meshing quality of the antenna base gear were obtained, including the size, shape and position of the contact impression area on the tooth surface. Finally, a set of digital measurement and evaluation method of gear meshing quality was developed to achieve the accurate evaluation of the gear meshing quality of the antenna base. The test results show that the linear weighted gray-scale method has better adaptability under different ambient brightness, and the error of feature extraction results is smaller than other methods.